La versión Browning - Asquith, Anthony, 1902-1968 (Regasa films, 1951)
Andrew Crocker-Harris is an embittered and disliked teacher of Greek and Latin at a British public school. After nearly 20 years of service, he is being forced to retire on the pretext of ...